Pengaruh Jumlah Penerbitan Surat Teguran, Surat Paksa, Dan Surat Sita Terhadap Penerimaan Pajak Kantor Pelayanan Pajak Tangerang Selatan - Saputra, Andrianto; Waluyo, Waluyo (Universitas Multimedia Nusantara, 2012)
Tax Revenue is one of the most important sources of revenue for making the state expenditure budget (APBN). The purpose of this study is to analyzing the influences of issuance Warning Letter (Surat Teguran), Letter of Tax Compulsion (Surat Paksa), and Confiscation Letter (Surat Sita) in partially and simultaneously to the tax revenue. Objects in this research are Tax Service Office (Kantor Pelayanan Pajak Pratama) Serpong and Tigaraksa at South Tangerang Tax Service Office for the period 2008-2011, the sample is selected by Convience Sampling Method. The data used in this research are numbers of Warning Letter, Letter of Tax Compulsion, and Confiscation Letter based on tax assisment letter (Surat Ketetapan Pajak) and Tax Collection Letter (Surat Tagihan Pajak) and Also Tax Revenue issued by the Tax Service Office serpong and Tigaraksa The result of this study are (1) Issuance of Warning Letter has not significant influenced to tax revenue, (2) Issuance of Letter of tax Compulsion has significant influence to tax revenue, (3) Issuance of Confiscation Letter has not significant influence to tax revenue, and (4) In Simultaneously Issuance of Warning Letter, Letter of Tax Compulsion, and Confiscation Letter has significant influence to tax revenue. Keyword: Confiscation Letter, Letter of Tax Compulsion, Tax Revenue, Warning Letter